Case Report: Pediatric CNS-isolated hemophagocytic lymphohistiocytosis secondary to uniparental disomy of PRF1 mutation - Xue, Jiao; Song, Zhenfeng; Zhao, Hongshan; Yang, Chengqing; Li, Fei; Yi, Zhi; Liu, Kaixuan; Zhang, Ying (Frontiers in Genetics, 2025)
BackgroundCentral nervous system-isolated hemophagocytic lymphohistiocytosis (CNS-HLH) is a rare disease caused by mutations in several genes.MethodsClinical information was obtained from medical records. Genetic analyses were performed using whole-exome sequencing (WES). NK cell function testing, Granzyme B staining, perforin staining, CD107a mobilization, and soluble CD25 levels were determined.ResultsWe report the case of a 5-year-old girl who presented with involuntary movements, an unsteady gait, and a progressively irritable temper. Cranial MRI revealed bilateral multifocal white matter abnormalities. The patient harbored a homozygous missense mutation in the PRF1 gene (NM_001083116.3), c.1349C > T (p.Thr450Met), which is a maternal uniparental disomy. Based on the phenotype and absence of perforin expression, the patient was diagnosed with CNS-HLH.ConclusionWe report a highly unusual case of CNS-HLH diagnosed by uniparental disomy of a PRF1 mutation. Exome sequencing should be considered in patients with chronic or recurrent brain inflammation who show partial or no response to conventional treatment regimens.